Gastroesophageal Reflux Disease: diagnosis and treatment - Michał Zdybel; Wojciech Sowiński; Adam Strzoda; Magdalena Kamińska; Anna Strzoda; Agata Strzoda; Agata Juda; Kornelia Rojek (Kazimierz Wielki University, 2023)
Introduction and purpose of the work: The mechanism of gastroesophageal reflux disease depends on reflux of gastric contents into the esophagus as a result of reduced tone of the lower esophageal sphincter. It presents itself in the form of symptoms coming from the esophagus, e.g. heartburn, as well as from outside of it. The aim of this paper is to collect and present current knowledge on gastroesophageal reflux disease as well as diagnosis and treatment through a review of the available literature.    Brief description of the state of the art:  Gastroesophageal reflux disease affects 18.1 - 27.8% of the US population and 8.8 - 25.9% of the European population. It is defined as the presence of troublesome symptoms or complications of reflux of gastric contents into the esophagus. The etiology consists of many factors, such as improper diet, and low physical activity. The disease can manifest itself with symptoms from and outside the esophagus. Diagnosis is based primarily on the history, and in the presence of typical symptoms, therapy with proton pump inhibitors is initiated. Endoscopy and reflux measurement is used when there is no response to pharmacotherapy. The basic drugs are proton pump inhibitors, other drugs are complementary to the basic therapy. A lifestyle change is also recommended. Surgical treatment is an alternative, but it may not be a permanent solution. Other treatments include endoscopic incisionless fundoplication and radiofrequency treatment of the lower esophageal sphincter.    Summary:  Diagnosis of gastroesophageal reflux disease begins with an interview with the patient and empirical pharmacotherapy. If treatment is ineffective, endoscopy and pH measurement are performed. Proton pump inhibitors are the most effective drugs in the treatment of the disease, other drugs are used as a supplement. Surgical and endoscopic procedures are an alternative to chronic pharmacotherapy.